Proterozoic structural highs beneath the Mackenzie Mountains, northwest Canada, discovered with filtered potential field and seismic data - Cook, Frederick (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary A linear belt of Mesoproterozoic (ca. 1.6Ga) structural highs, some with more than 6-7 km of subsurface relief, underlies the Mackenzie Mountains in northwestern Canada over a distance of at least 1000km from southeast to northwest. The trend is visible on isostatic gravity data that were bandpass filtered to wavelengths appropriate for intracrustal features, and on seismic reflection profiles that have images of buried Proterozoic antic lines associated with the gravity highs. The combination of filtered potential field data tied to seismic images of subsurface structure in key areas provides a powerful method to map intracrustal structures at long distances away from cross-sectional profiles.